Mgo Nanoparticles Coated with Polyethylene Glycol as Carrier for 2-Methoxyestradiol Anticancer Drug - Orihuela-Diaz, P; Reuquen-Lopez, P; Zapata-Ramirez, P; Guajardo-Correa, E (Public Library of Science, 2019)
Novel Magnesium Oxide (MgO) nanoparticles (NPs) modified with the polymer polyethylene glycol (PEG) were synthesized as carrier for the anticancer drug 2-Methoxyestradiol (2ME) to improve its clinical application. The functionalized NPs were characterized by Infrared spectroscopy with Fourier transform to elucidate the vibration modes of this conjugate, indicating the formation of the MgO-PEG-2ME nanocomposite. The studies of absorption and liberation determined that MgO-PEG-2ME NPs incorporated 98.51 % of 2ME while liberation of 2ME was constant during 7 days at pH 2, 5 and 7.35. Finally, the MgO-PEG-2ME NPs decreased the viability of the prostate cancer cell line LNCap suggesting that this nanocomposite is suitable as a drug delivery system for anticancer prostate therapy. © 2019 Alfaro et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.